A study on COVID – 19’s effect on Teaching Learning Process in Engineering Educationin the Post Pandemic Indian Education Market - Dr. Soundarya N. (International Journal of Advanced Science and Technology, 2020)
As India is moving towards knowledge driven economy, its strength depends upon the capabilities of its citizens. The key to develop a knowledge driven society is to create good Engineering graduates with sound technical knowledge who can be Entrepreneurs, Government executives or even Educators.The pedagogy for engineering education has not changed much in the past hundreds of years. With technology advancements in almost all fields Engineering Education is still practising the age - old traditional teaching methods. To revolutionize Engineering education the integration of technology in teaching methods has become the need of the hour. Also teaching has been one of the professions where the educators never enjoyed longer vacations or work from home due to the rigid brick wall teaching environment. This COVID -19 pandemic has made the entire country go into stages of lockdown. Engineering colleges were closed and the colleges cannot suffer loss of contact hours between the teachers & the students. Hence, the engineering colleges were forced to adopt online teaching methodology with little or no preparation in hand. On the positive side this can be seen as an opportunity to transform towards Blended learning in Engineering Education. This paper aims in understanding the educational scenario world-wide during the pandemic, the problems faced during the lockdown, analysing the factors affecting blended learning and recommends tools and suggestions so that Engineering Education can have a smooth transition towards Blended learning without much hassles.